The Implementation of PAKEM Learning Method to Improve the Competence of the Students in Using Proverbs in Writing Among the Students of Grade V of Public Elementary School 104189 Datar City - Poniman, Hendro; Kartolo, Rahmat (International Journal of Educational Research Excellence (IJERE), 2024)
The issues in this study is: How to improve the ability to use proverbs in the essays of fifth grade students of SD Negeri 104189 Kota Datar? The purpose of this study is to describe the improvement of the ability to use proverbs in the essays of the students of the fifth grade of SD Negeri 104189 Kota Datar. The type of research used is Classroom Action Research (PTK) using 3 cycles, namely cycle I, cycle II and cycle III, broadly speaking, there are four stages that are passed in carrying out Classroom Action Research (PTK), namely planning, implementing, observing and reflecting. The subjects in this study were fifth grade students of SD Negeri 104189 Kota Datar, a total of 39 people. The findings showed that the application of PAKEM method with proverbial teaching aids by the teachers of Grade V students of SD Negeri 104189 Kota Datar, as evidenced by the increase in student activity for each index. In the first indicator, the number of very active pupils rose from 4 in the first cycle to 10 in the second, and again to 21 in the third. The other indicators of student activity continued to increase in each cycle. The increase in the ability to use proverbs in the essays of fifth grade students of SD Negeri 104189 Kota Datar occurred significantly, this can be seen from the average value of the ability to use proverbs in cycles I, II and III. From cycle I to cycle II, the average ability to use proverbs increased from 48.84 to 69.23, an increase of 20.39, likewise from cycle II to cycle III increased from 69.23 to 75. 46 again increased by 6.23. Logically, from Cycle I to Cycle III it increased by 26.62.